Oestrogen receptor proteins in malignant and fetal pancreas. - Greenway, B (1981)
High levels of high-affinity oestrogen binding were detected in cytosolic and nuclear fractions of tumour tissue from six patients with pancreatic carcinoma. Similar binding was found in fetal but not in normal adult pancreas, making depression of fetal genes a possibility. Specific androgen binding was not detectable. These findings suggest that anti-oestrogen treatment may offer a new approach to the treatment of pancreatic carcinoma.